Enucleation and Dermato-fat Graft for Retinoblastoma Management : A Case Report: Poster Presentation - Case Report - Resident - SIMANJUNTAK, dr. AGNES ANGELA MAHDALENA; Anne, Umboh; Freili, Akay (Majalah Oftalmologi Indonesia, 2023)
Introduction : Retinoblastoma is the most common intraocular malignant tumor found in children before 3 years old can occur unilaterally, bilaterally, hereditary or sporadic. Incidence of about 1:14,000-20,000 individuals. This tumor originated from embryogenic retinal cells. Retinoblastoma gene (RB1) located in the 13q14 chromosome Case Illustration : A 3-year-old girl presented with leukocoria. Her parents notice whitish in her right eye swollen, teary, painful since 2 months ago. No family history. Visual acuity (VA) on the oculus dextra ( OD) no light perception, oculus sinistra (OS) 6/6. Intraocular pressure on OD n-1/palpation, OS n/palpation. Examination under anasthesia for diagnostic found there weren’t palpebral edema, conjunctival injection, hazy cornea, pupil, lens couldn’t be evaluated on OD. Ultrasound showed sugest vitreous seeding and ptisis. CT scan showed solid mass with calcification and diagnosed retinoblastoma stage group E. Patient was treated with chemoreduction using Vincristine, Etoposide, Carboplatine combined enucleation with dermato-fat graft. We did nervus opticus dissection and histopathological examination which showed retinoblastoma. Discussion : The common signs of retinoblastoma is leukocoria. The priority is saving life followed by globe preservation. Treatment based on the stage of the disease. We did chemotherapy in this patient, followed by enucleation and dermato-fat graft. Enucleation stills the main therapy for saving life with nervus opticus dissection as possible. Dermato-fat graft has been shown to grow along with the expanding orbit in children therefore shows cosmetics. Conclusion : This report illustrates a case of Retinoblastoma. The chemotherapy and enucleation using safe dermato-fat graft procedure with implant followed by a well fitted prosthesis for better cosmetics